Tratamento de águas residuárias de laticínio em reatores anaeróbios alternativos - Santos, Ariane Chiareli dos [UNESP] (2015)
The performance of two anaerobic systems for treating wastewater from dairy products industries was evaluated. The first systems composed by horizontal-flow anaerobic reactors combined with subsurface ferti-irrigation (SAHFS) culture cherry tomato were fed with wastewater from the dairy products industry. Different support materials, crushed stone and tire strips, were used in order to verify the best materials which provide a better adherence to microorganisms, thereby forming a biofilm for the anaerobic treatment system. The chemical oxygen demand (COD) removal efficiency obtained was 80 % and 90 % for the material crushed stone and tire strips (Systems A and B) respectively. Also different feed concentrations of wastewater were tested, and 97 % of COD removal efficiency was obtained for the system feed with 1 and 6 g L-1 COD (system D and E, respectively). For the system feed with 10 g L-1 COD (system F) the COD removal efficiency was 92%. The results obtained in the subsurface ferti-irrigation culture cherry tomato for the systems D, E and F, were 80, 120 and 70 cm for culture plants growth and for the leaf area mass were 7.000, 18.000 and 6.000 cm2, respectively. The second system used for the treatment of wastewater from dairy industry was composed by an inverted anaerobic sludge blanket reactor (IASB). A new configuration of high rate anaerobic reactor with the aim to treating wastewater with large amounts of lipids, as in the case of dairy industries wastewaters. The reactor operated in cycles feed/reaction, so that the microbial consortia of the reactor could degrade the organic matter. During the cycles, different Hydraulic Retention Times (HRT) were tested of 1, 0.67 and 0.33 days and also different organic load rate (OLR) of 2.4 3.6 and 7.2 g COD L-1. It was possible to verify values of COD removal of 90% in all HRT and OLR used. The production of methane during the experiment was 70 - 80 L CH4 day-1. The percentage of organic ...